INCIDENCE OF JOB MISMATCH AMONG TVL GRADUATES IN BUTUAN CITY, PHILIPPINES - Autentico, Jondie Mark; Alerta, Gilbert (PEOPLE: International Journal of Social Sciences, 2020)
Landing a job is one of the expected outcomes behind the huge investment of Philippine education in the implementation of Technical Vocation and Livelihood (TVL). But job far from TVL specialization is a failure to the curriculum. This study assesses the incidence of job mismatch among employed pioneering batches (2018 and 2019) of TVL graduates in Butuan, City Philippines. Factors of job mismatch are also analyzed. A total of 269 employed TVL graduates were surveyed using a researcher-made questionnaire. Statistical analysis reveals a 64% (171) mismatch incidence. Logistic regression analysis further shows that national certification, faculty and instruction, job experience, workers compensation, and family support are significant factors to job mismatch incidence. The study concludes that mismatch between job and skill is highly evident. The findings of this study serve as bases in the creation of intervention initiatives that will improve the implementation of the TVL program.